The utility of a standardised breath sampler in school age children within a real-world prospective study. (1st April 2022) - Bhavra, K K; Wilde, M; Richardson, M; Cordell, R; Thomas, P; Zhao, B; Bryant, L; Brightling, C E; Ibrahim, W; Salman, D; Siddiqui, S; Monks, P; et al.
Abstract: Clinical assessment of children with asthma is problematic, and non-invasive biomarkers are needed urgently. Monitoring exhaled volatile organic compounds (VOCs) is an attractive alternative to invasive tests (blood and sputum) and may be used as frequently as required. Standardised reproducible breath-sampling is essential for exhaled-VOC analysis, and although the ReCIVA (Owlstone Medical Limited) breath-sampler was designed to satisfy this requirement, paediatric use was not in the original design brief. The efficacy of the ReCIVA at sampling breath from children has been studied, and 90 breath-samples from 64 children (5–15 years) with, and without asthma (controls), were collected with two different ReCIVA units. Seventy samples (77.8%) contained the specified 1 l of sampled-breath. Median sampling times were longer in children with acute asthma (770.2 s, range: 532.2–900.1 s) compared to stable asthma (690.6 s, range: 477.5–900.1 s; p = 0.01). The ReCIVA successfully detected operational faults, in 21 samples. A leak, caused by a poor fit of the face mask seal was the most common (15); the others were USB communication-faults (5); and, a single instance of a file-creation error. Paediatric breath-profiles were reliably monitored, however synchronisation of sampling to breathing-phases was sometimes lost, causing some breaths not to be sampled, and some to be sampled continuously. This occurred in 60 (66.7%) of the samples and was a source of variability. Importantly, multi-variate modelling of untargeted VOC analysis indicated the absence of significant batch effects for eight operational variables. The ReCIVA appears suitable for paediatric breath-sampling. Post-processing of breath-sample meta-data is recommended to assess the quality of sample-acquisition. Further, future studies should explore the effect of pump-synchronisation faults on recovered VOC profiles, and mask sizes to fit all ages will reduce the potential for leaks and importantly, provide higher levels of comfort to children with asthma.